Internetforen für Patienten mit Prostatakrebs = Online support groups for patients with prostate cancer - Huber, Johannes; Maatouk, Imad; Ihrig, Andreas (Aktuelle Urologie, 2019)
Background Online support groups are discussion boards on the internet in which users exchange experience, advice and information. The Bundesverband Prostatakrebs Selbsthilfe e. V. (BPS) operates the largest German-language internet forum for prostate cancer patients. Materials and Methods Several aspects of the BPS Forum were examined: content analysis, language use and interaction, influence on treatment decisions, comparison with conventional face-to-face support groups, and use by relatives and friends. Results The online support group is dominated by a tentative style of communication with reserved language features. In addition to the exchange of information, emotional support seems to be very welcome to many users and represents an essential part of the exchange. The use of the internet forum leads to a change in the initial treatment decision in 29 % of patients. In comparison with the general population, rates of patients with anxiety and depression were two to three times as high among the users. Compared with the patients themselves, family members in particular had higher values for anxiety and depression and described a higher rate of metastatic diseases in the patients known to them. Users of the online support group were younger, had a higher educational level and a higher income than participants in conventional face-to-face support groups. Conclusions Online support groups are rated positively by their users and contribute to the acquisition of information and emotional support. They probably have a significant influence on the primary treatment decision and thus actively shape the reality of care for prostate cancer patients.
Gesehen am 04.11.2019